1990
DOI: 10.1111/j.1365-2265.1990.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Free 1,25‐dihydroxyvitamin D and the Free 1,25‐dihydroxyvitamin D Index During a Longitudinal Study of Human Pregnancy and Lactation

Abstract: The changes in three different indices of 1,25-dihydroxyvitamin D (1,25(OH)2D) biological activity were studied longitudinally in 35 women during late pregnancy and lactation and in 26 control women. Measurements were made of maternal serum total 1,25(OH)2D and free 1,25(OH)2D concentration (by centrifugal ultrafiltration) and the free 1,25(OH)2D index (the molar ratio of total 1,25(OH)2D and vitamin D binding protein (DBP]. During late pregnancy total 1,25(OH)2D concentrations were significantly elevated when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 26 publications
4
44
1
Order By: Relevance
“…B) HUMAN DATA. Similar to the findings in the animal models, cross-sectional studies have found a doubling or tripling of serum calcitriol that begins early in the first trimester and reaches the highest levels in the third trimester (81,207,287,324,387,578,599,632,764,981,987). Longitudinal studies have confirmed a progressive increase in free and bound calcitriol that is maintained to term (33, 81,764,809,813,959,987).…”
Section: Calcitriol and Calcidiolsupporting
confidence: 59%
See 1 more Smart Citation
“…B) HUMAN DATA. Similar to the findings in the animal models, cross-sectional studies have found a doubling or tripling of serum calcitriol that begins early in the first trimester and reaches the highest levels in the third trimester (81,207,287,324,387,578,599,632,764,981,987). Longitudinal studies have confirmed a progressive increase in free and bound calcitriol that is maintained to term (33, 81,764,809,813,959,987).…”
Section: Calcitriol and Calcidiolsupporting
confidence: 59%
“…B) HUMAN DATA. Free and total calcitriol falls to normal during postpartum (206,439,578,746,809,987) and remains normal throughout lactation and postweaning (156,157,206,207,348,385,470,505,632,764,805,871,987). One study found that extended lactation (Ͼ6 mo) was associated with higher calcitriol (348), another report found that calcitriol increased during the postweaning interval of bone recovery (871), and a third report found that calcitriol was 10% higher during lactation and that this persisted during the post-weaning interval (454).…”
Section: Calcitriolmentioning
confidence: 95%
“…Despite these signi¢cant changes in the bone turnover markers, it is of note that the serum albuminadjusted calcium values did not change throughout pregnancy. Others have observed an increase in the adjusted calcium, 21 which would correlate with an increase in 1,25(OH) 2 D, 6 while a slight decrease has been observed in ionized calcium. 22 Although a trend towards an increasing total calcium was observed in our data, this was not signi¢cant, and this discrepancy may be a drawback of the limited number of sampling points in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been suggested that this may be driven by parathyroid hormone (PTH); 7 however, more recent studies have shown a signi¢cant decrease in PTH during pregnancy and have suggested the possible involvement of parathyroid hormone -related protein (PTHrP). 8,9 Bone histology suggests an increase in resorption at this time, 10 and this is supported by recent studies of biochemical markers of bone turnover.…”
Section: Introductionmentioning
confidence: 99%
“…This was initially thought to be mediated by 1,25(OH) 2 D, as it is known that serum levels of 1,25(OH) 2 D increase early in pregnancy and peak at twice the non-pregnant range 33,43,[48][49][50][51][52][53] . However, free concentrations of 1,25(OH) 2 D appear to increase only during the third trimester, and the peak in intestinal calcium absorption occurs well before this 54,55 .…”
Section: Vitamin D and The Regulation Of Mineral Homeostasis During Pmentioning
confidence: 99%